O legado cyberpunk: direitos fundamentais na era da informação - França, Márcio José Moreira (2022)
The present thesis aims to establish a dialogue between the cyberpunk science fiction subgenre and the issue of fundamental rights in the information age, analyzing especially the matter of identity in this context. The methodology employed in the research is based on the critical analysis of selected works of cyberpunk and contrasting them with contemporary scenarios, also observing the historical evolution of the concept of identity and the social models that accompanied it. The question that is presented is that we’re increasingly close to live in a society like those we’ve been warned about in fiction, also aiming to bring about suggestions on how to avoid such a future. Just like it’s been described by the expression “high tech, low life”, which defines cyberpunk, we’re in a scenario where technological progress walks hand in hand with imminent social collapse.